Analysis of The Influence of The Tourism Sector on The Gross Regional Domestic Product of Bali Province 2017-2023 - Nadia Oktaviani (Jurnal Wacana Ekonomi, 2025)
Economic growth is one of the indicators used to calculate the success of a country's economy. Economic growth is formed from various economic sectors, which are a reflection of the level of economic growth that is occurring. This study was conducted to determine and analyze the influence of the tourism sector, consisting of variables such as the number of foreign tourist visits, the number of hotels, and the number of flights, on the Regional Domestic Product (PDRB) in Bali Province. The approach used in this study is a quantitative descriptive approach. The data in this study uses secondary data obtained from various official sources such as BPS Indonesia, BPS Bali Province, and the Bali Tourism Office from 2017-2023. This study uses a time series data regression analysis method with the Error Correction Model (ECM). The results show that in the short term, the number of foreign tourist visits has a significant positive effect on GRDP, while the number of hotels and flights has no effect and has a negative effect on GRDP. In the long term, the three independent variables have no effect and have a negative effect on GRDP. Keywords: tourism sector, GDP, economic growth, time series data